1996
DOI: 10.1017/s0967199400002951
|View full text |Cite
|
Sign up to set email alerts
|

Comparative glucose and fructose incorporation and conversion by in vitro Produced bovine embryos

Abstract: SummaryWe have investigated the quality of bovine IVM/IVF embryos co-cultured on Vero cells. Blastocyst cell numbers are very similar to those obtained in vivo, and higher than those obtained by co-culture with oviduct cells. The metabolism and conversion of fructose and glucose are not equivalent even though carbon dioxide production is similar and increasing from morula to blastocyst. Formation of free amino acids and incorporation into proteins are higher and faster for glucose than for fructose, but this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Incorporation and oxidation of radiolabel glucose, fructose, and methionine by porcine oocytes All radioactive substrates, 14 C-glucose (spec. act: 185 MBq/ mmol), 14 C-fructose (spec. act: 212 MBq/mmol), and 14 C-methionine (spec.…”
Section: Assessment Of Oocyte Nuclear Status and Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation and oxidation of radiolabel glucose, fructose, and methionine by porcine oocytes All radioactive substrates, 14 C-glucose (spec. act: 185 MBq/ mmol), 14 C-fructose (spec. act: 212 MBq/mmol), and 14 C-methionine (spec.…”
Section: Assessment Of Oocyte Nuclear Status and Fertilizationmentioning
confidence: 99%
“…Like glucose, fructose is capable of entering the glycolytic pathway. In addition, fructose is present in rabbits [10] and bovine [11] reproductive tracts and effectively supports embryonic development in hamster [12], bovine [13,14], mouse [15], porcine [16], and human embryos [17]. Furthermore, fructose can increase the total cell numbers in both hamster [12] and bovine blastocysts [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that inclusion of glucose in culture media affects negatively the development of early-stage embryos in hamsters (Schini & Bavister, 1988;Barnett & Bavister, 1996;Barnett et al, 1997), mice (Chatot et al, 1989;Lawitts and Biggers, 1991;Scott & Whittingham, 1996), rats (Kishi et al, 1991;Miyoshi et al, 1994), cattle (Kim et al, 1993), sheep (Thompson et al, 1992) and humans (Conaghan et al, 1993;Quinn, 1995). It has been reported that fructose is present in the reproductive tract of cattle (Suga & Masaki, 1973) and is utilized by bovine embryos in vitro (Guyader-Joly et al, 1996). As with glucose, fructose can be metabolized through the glycolytic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Some of those mechanisms could be critical for the compaction of the morula and the protection against oxidative stress (Surani, 1979;Flood & Wiebold, 1988;Wales & Hunter, 1990;Thompson et al, 1992a;Rieger, 1992;Rieger et al, 1992;Barnett et al, 1993;Guyader-Joly et al, 1996;Gardner, 1998;Khurana & Niemann, 2000). However, ruminant embryos do not seem to store glycogen (Thompson et al, 1995;Guyader-Joly, 1996). The increase in glucose uptake observed with blastocyst formation, expansion and hatching seems to be related mainly to the increasing number of cells, as no significant difference was detected if the uptake was expressed on a per cell basis.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, the shift towards glucose use seems to depend on the developmental stage (not the age or the cell number of the embryo) and requires transcription of the embryonic genome (Martin & Leese, 1999). In various species, the morula and blastocyst stages are characterised by a further increased use of exogenous glucose for energy production but also as a precursor of triglycerides, amino acid and glycoproteins implicated in compaction (Surani, 1979;Flood & Wiebold, 1988;Wales & Hunter, 1990; Thompson et al, 1992a;Rieger, 1992;Rieger et al, 1992;Barnett et al, 1993;Guyader-Joly et al, 1996;Gardner, 1998;Khurana & Niemann, 2000). Total glucose metabolism doubles between the morula and expanded blastocyst stages in cattle embryos (Tiffin et al, 1991).…”
Section: Introductionmentioning
confidence: 99%